Networks-Based Marketing Technology Small and Medium Enterprises (UKM) D'triejie Kalimango Village, Alas District, Sumbawa Regency - Surjanah, Surjanah; Saleh, Muhammad; Jaya, Ahmad (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2022)
In the current era of globalization, the development of technology and information is very fast and increasingly widespread. As well as the sudden restriction of human movement due to the covid-19 pandemic. Utilization of information technology in running a business or often known as e-commerce for small and medium enterprises (SMEs) can provide flexibility in production, enabling faster delivery to customers. Designing, creating, implementing and knowing influencer use system information marketing web based for sale through electronic media (e-commerce) in D'Triejie Small and Medium Enterprises (UKM). Study this including in type research and development. Development packaged e-learning in online form on website: https://c89f-114-122-140-135.ap.ngrok.io/yanti/index.php Development the e-commerce use application programs open source Joomla which is uploaded and installed on the domain and hosting that has been rented During one year. This e-commerce has validated by experts material and media experts, as well has follow stages in development revised until obtained results expected e-commerce. Developed e-commerce then tested on the community. E-commerce own excess could displays goods accompanied with supporting multimedia files as images, video, audio and also flash animation. How to design, create, implement and sell sales results using a web-based marketing information system for sales through electronic media. Knowing the effect of electronic (e-commerce) usage on D'TrieJie's small and medium. Enterprises (UKM) D'TrieJie's small and medium enterprises (UKM) are located on Jl. Prona Rt.02. Rw.03 Kalimango village, Alasdistrict, Sumbawa Regency small and medium enterprises (UKM) D'TrieJie's is one of the home-based businesses engaged in culinary, fruit, juice, plastic etc. Initially D'TrieJie's small and medium Enterprises (SMEs) sold several types of fruit, including oranges, grapes, apples, pears and so on. Over time D'TrieJie's small and medium Enterprises (SMEs) expanded their business by adding more products to the market, namely fruit salad, fruit salad pudding and various fruit drinks. Furthermore, D'TrieJie's small and medium enterprises (UKM) businesses increased their products by marketing packaging containers for salads, drinks and so on.